Synthesis of Alumina Using Urea and Glycine as Fuel: Mono Fuel Approach - Saurabh Sharma,; Dr Jitendra Kumar Gupta, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this Paper, “Synthesis of Alumina using urea & Glycine as fuel: Mono fuel approach”, chosen as research work, here two fuel types (urea & glycine) were used in two different experiments, along with aluminium nitrate as oxidizer, to synthesise alumina powder. Three samples for each fuel type were prepared with variation in fuel to oxidizer ratio, in reference to stoichiometric ratio. Samples were further characterized with respect to observation of combustion flame, XRD and SEM analysis. Results obtained are in good agreement with available literature and almost as expected, from application point of view.
Keywords: Urea; Glycine; alumina; SHS; Synthesis